The role of knowledge in improving attitudes and behaviors of stunting prevention in pregnant women - Adam, Nilawati; Fitrianingsih, Julia; Basir, Muhammad (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Knowledge about stunting prevention in pregnant women plays an important role in shaping attitudes and behaviors that support stunting prevention efforts. This study analyzes the relationship between knowledge, attitudes, and behaviors related to stunting prevention in pregnant women. Research Methodology: The design of this study is quantitative, using a descriptive design and a cross-sectional approach. The research design used is correlational, using the Cross-Sectional approach and sampling techniques using Probability Sampling with a simple random sampling type. Result: The results of the study showed that the relationship between pregnant women's knowledge about balanced nutrition and attitudes and behaviors (efforts) to prevent stunting in toddlers at the Bojo Baru Health Center obtained a significant value of p = 0.008 (0.008 < 0.05), that the majority of pregnant women's knowledge levels about balanced nutrition with efforts to prevent stunting in the good category were 45 people (75%). Conclusion: Pregnant women's knowledge has a significant role in shaping attitudes and behaviors that support stunting prevention. Pregnant women with a higher knowledge level tend to show a more positive attitude and better behavior in stunting prevention. Therefore, increasing knowledge through education and counseling is very important to encourage pregnant women to take appropriate preventive measures to reduce the risk of stunting in children. More intensive and structured education programs must be strengthened as a preventive effort to overcome the community's stunting problem